2011
DOI: 10.1007/s00248-011-9974-9
|View full text |Cite
|
Sign up to set email alerts
|

Change in Land Use Alters the Diversity and Composition of Bradyrhizobium Communities and Led to the Introduction of Rhizobium etli into the Tropical Rain Forest of Los Tuxtlas (Mexico)

Abstract: Nitrogen-fixing bacteria of the Bradyrhizobium genus are major symbionts of legume plants in American tropical forests, but little is known about the effects of deforestation and change in land use on their diversity and community structure. Forest clearing is followed by cropping of bean (Phaseolus vulgaris) and maize as intercropped plants in Los Tuxtlas tropical forest of Mexico. The identity of bean-nodulating rhizobia in this area is not known. Using promiscuous trap plants, bradyrhizobia were isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 75 publications
5
21
0
2
Order By: Relevance
“…In the present study, the population abundances, community structures, and diversity of effective soybean rhizobia varied drastically among the treatments ( Fig. 1 and Table 1), reflecting the fact that the rhizobia were strongly affected by soil management, like the cropping system, land use patterns, and fertilizer input, which were similar in some respects to previous reports (12,58,60) and also provided some new information.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the present study, the population abundances, community structures, and diversity of effective soybean rhizobia varied drastically among the treatments ( Fig. 1 and Table 1), reflecting the fact that the rhizobia were strongly affected by soil management, like the cropping system, land use patterns, and fertilizer input, which were similar in some respects to previous reports (12,58,60) and also provided some new information.…”
Section: Discussionsupporting
confidence: 71%
“…Second, the other treatments, except for GL, had lower diversity indexes, and no Bradyrhizobium sp. II bacteria were isolated (Table 1), demonstrating that mowing grass or converting grassland to agricultural use decreased the diversity of soybean rhizobia, which was similar to the effects of deforestation on native Bradyrhizobium communities (60). Third, fertilization did not change the genospecies composition of soybean rhizobia but decreased the diversity of the rhizobia, as shown by the increased relative proportion of Bradyrhizobium sp.…”
Section: Discussionmentioning
confidence: 80%
“…Reports on B. pachyrhizi are rare, and not much is yet known about its distribution and ecology. A high proportion of B. pachyrhizi bacteria was detected under different land use systems in Mexican tropics using cowpea and siratro (Macroptilium atropurpureum) as trap plants (56). The Mexican sampling sites were characterized by a warm, humid climate and acid soils (pH 4 to 6), strikingly matching the warm, semihumid climate with an annual mean rainfall of 987 mm and an annual mean temperature of 20.4°C (57) in the Cusseque area.…”
Section: Pachyrhizimentioning
confidence: 99%
“…Such genes are present in sv. tropici strains that are also Leucaena symbionts [10]. Like R. etli strain CFN42, Mim1 may produce nodulation factors bearing carbamoyl groups at their non reducing end residues but the position of these decorations must differ because their pSyms encoded distinct carbamoyl transferases, NolO in CFN42 and NodU in Mim1.…”
Section: Resultsmentioning
confidence: 99%
“…phaseoli and not in sv. mimosae served as a molecular basis to distinguish these symbiovars [10, 11]. Phylogenies indicated that symbiovar mimosae and phaseoli nifH genes were related [9] and similar to the corresponding gene in sv.…”
Section: Introductionmentioning
confidence: 99%